Vilfredo Pareto on Culture and Derivations: Virtuism as a Logicizing Perversion - Lombardinilo, Andrea (Italian Sociological Review, 2024)
The essay investigates the sociological premises at the basis of Vilfredo Pareto’s tenet of “virtuism” as it complies with his effort to combine sociology, literature and communication and deal with the conservative action fostered by the Catholics against the diffusion of immoral contents and images. The criticism of any form of censorship concerns the celebration of art and the opposition to fanaticism (both religious and political) undermining the everlasting power of culture. In Pareto’s perspective, the juxtaposition of residues and derivations, along with the dialectics of logical and non-logical actions, sheds light on the argumentative techniques that social actors exploit to logically legitimate actions, gestures and decisions that usually appear to be inspired by prejudices, false opinions and cultural heritage, as Pareto scornfully underlines in The Virtuist Myth and Immoral Literature (1914). Two events impose a sharp reflection on the tenet of morality within the public sphere and the impact that images, texts and symbols have on individual and collective sensitivity: the covering of ancient Roman statues in the Capitoline Museum in Rome for the visit of an Iranian president, and the removal of a seventeenth-century painting of a butcher from a Cambridge (UK) university dining hall after protests by vegan students. Such tenets and impacts were illustrated by Federico Fellini in The Temptation of Dr. Antonio (1962). Once again, logical and non-logical actions comply with cultural beliefs and communicative practices, at a time ruled by new forms of moral and immoral display.